2021
DOI: 10.1111/mve.12532
|View full text |Cite
|
Sign up to set email alerts
|

Migration and season explain tick prevalence in Brazilian birds

Abstract: Neotropical birds are mostly parasitized by immature ticks and act as reservoir hosts of tick‐borne pathogens of medical and veterinary interest. Hence, determining the factors that enable ticks to encounter these highly mobile hosts and increase the potential for tick dispersal throughout migratory flyways are important for understanding tick‐borne disease transmission. We used 9682 individual birds from 572 species surveyed across Brazil and Bayesian models to disentangle possible avian host traits and clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Therefore, the presence of migrants in a community could impact local parasite-host dynamics. Indeed, previous research has associated the presence of migratory birds with variation in tick prevalence and haemosporidian prevalence and richness within the local community in South America (de Angeli Dutra et al 2021b;Fecchio et al 2021). In contrast, despite the fact that only partially migratory hosts presented higher closeness centrality when evaluated separately, de Angeli Dutra et al (2021a) observed that only fully migratory birds harbor higher prevalence and richness of haemosporidian parasites.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the presence of migrants in a community could impact local parasite-host dynamics. Indeed, previous research has associated the presence of migratory birds with variation in tick prevalence and haemosporidian prevalence and richness within the local community in South America (de Angeli Dutra et al 2021b;Fecchio et al 2021). In contrast, despite the fact that only partially migratory hosts presented higher closeness centrality when evaluated separately, de Angeli Dutra et al (2021a) observed that only fully migratory birds harbor higher prevalence and richness of haemosporidian parasites.…”
Section: Discussionmentioning
confidence: 95%
“…At the same time, migrants can represent an opportunity for parasites to increase their distribution worldwide, as infected migrant individuals transport their pathogens through their routes and stopovers, therefore, providing new opportunities for host switching into new environments and resident species (Altizer et al 2011;de Angeli Dutra et al 2021b;Poulin and de Angeli Dutra 2021). Indeed, the presence of migratory individuals can also affect local parasite transmission, altering parasite prevalence and richness within resident host communities (Bauer and Hoye 2014;de Angeli Dutra et al 2021b;Fecchio et al 2021). However, despite the fact migration can modulate parasite-host interaction, only a few studies have addressed the implications of host migration for parasite ecology and evolution (Poulin and de Angeli Dutra 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Neotropics, tick infestation rates range from 8 to 28%, while in temperate regions, values range from 4 to 70% (Klich et al 1996 ; Morshed et al 2005 ; Miller et al 2016 ; Domínguez et al 2019 ). It has been broadly suggested that tick infestation risk in birds is mediated by environmental factors such as geographic location (e.g., latitude), climatic conditions (e.g., temperature and precipitation), and ecological factors such as habitat type and disturbance (e.g., fragmentation), and bird species richness (Lindgren et al 2000 ; Ogrzewalska et al 2011 ; Jore et al 2014 ; Fecchio et al 2021a ; Lilly et al 2022 ). In this context, a comprehensive knowledge of the environmental and ecological factors influencing tick infestation in wild birds across the Americas is crucial for understanding the dynamics of tick-borne parasite transmission in the context of potential climate change scenarios, habitat disturbance, and biodiversity loss.…”
Section: Introductionmentioning
confidence: 99%
“…Migratory birds represent around 19% of all avian species and can have profound effects on host–parasite relationships at the population and community levels (Bauer and Hoye, 2014 ). Earlier studies have revealed that migratory behaviour can both protect hosts against parasites or increase their risk of infection, with migratory species subject to either lower or higher parasite prevalence and richness, depending on the taxa under study (Koprivnikar and Leung, 2015 ; Teitelbaum et al ., 2018 ; de Angeli Dutra et al ., 2021 a ; Fecchio et al ., 2021 ). These contrasting observations result from a balance of pressures between escaping parasites, increased exposure to infective stages and the physiological cost of migration (Poulin and de Angeli Dutra, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, parasite virulence favours the emergence of migration as an escape mechanism as higher virulence increases the benefit of escaping from pathogens (Balstad et al ., 2021 ). The proportion of migrant individuals in a local bird assemblage may also alter local parasite prevalence and richness (de Angeli Dutra et al ., 2021 b ; Fecchio et al ., 2021 ). Indeed, migrant birds present greater centrality values within avian–haemosporidian networks (de Angeli Dutra et al ., 2021 c ) and can drive the expansion of geographical range of haemosporidian parasites by introducing them into new regions and habitats (de Angeli Dutra et al ., 2021 b ).…”
Section: Introductionmentioning
confidence: 99%